(untitled) (Global Journal of Science Frontier Research, 2026)
The dirty graphene wave has swept across the entire scientific world. And it has once again confirmed that quasi-scientific speculations without taking into account the Fundamental Laws only lead to huge waste of effort and resources. But this wave was able to arise because it was not out of nowhere. Nobel laureates, who were in a hurry to get money, simply stated what was, in principle, expected, but from the prevailing erroneous Model of Graphite. And, thus, with their ignorant “proofs” they led the research of thin graphite layers down the wrong path. The analysis carried out in this article, using the example of the SIMPLE Graphite Material and its ultra-thin layers in a congruent matrix of boron nitride, shows how it is possible to create a whole class of fundamentally new, real materials. The ideal correct structure of thin layers of rhombohedral graphite, down to mono atomically thin, can be obtained not for a freely suspended (on sticky tape) film and not due to Van der Waals forces, as graphenologists claim, but in a congruent matrix -a crystal of rhombohedral boron nitride. And a radical improvement in the properties of materials can be obtained on the basis of truly unusual properties of such graphite layers with an undamaged surface, and in no way on the basis of a graphene model that does not correspond to the real material.